F.Y. Kohn’s contribution to the ethnographic research of Tuva - Mannay-ool, Mongush H. (The New Research of Tuva, 2010)
The article tells about a life journey and a major efforts of Felix Yakovlevich Kohn in studying the Tuvan national ethnography. In 1902-1903 he had a big expedion to Tuva and gathered a lot of ethnographical materials, which became a foundation for his books “Expedition to Soyotia”. This work appears to be the first big publication over Tuvan ethnography and it is difficult to overestimate the scientific importance of this work. Also of important value are unique photos of material and spiritual culture objects. Exceptionally valuable and rich scientific legacy of Felix Yakovlevich are diaries. These diaries have to be studied in the future.
Keywords: F. Y. Kohn; ethnography; Tuva; expedition; materials; diaries